Development of Corporate-Based ZISWAF Fundraising Model in Realizing SDGs from Maqashid Syariah Perspective - Dede Al Mustaqim Mustaqim (International Economic and Finance Review, 2024)
This study examines the corporate-based ZISWAF (Zakat, Infaq, Sedekah, Wakaf) fundraising model grounded in Maqashid Syariah with the hope of contributing to the achievement of SDGs (Sustainable Development Goals) and realizing the welfare of the community. The descriptive qualitative research design employs literature review to gather data, revealing the significant potential of this model in reaching its objectives. Research findings indicate that the model excels in alignment with Islamic values, efficiency and effectiveness in fund management, sustainability of funding, and wide-ranging impact through extensive corporate outreach. To develop and implement this model, it requires strengthening collaboration among corporations, ZISWAF institutions, government, and other stakeholders, developing programs focusing on SDGs and community welfare, enhancing education for corporations and the public, reinforcing supportive regulations, and conducting regular monitoring and evaluation to ensure its effectiveness. The corporate-based ZISWAF fundraising model grounded in Maqashid Syariah is regarded as an innovative solution that can bring broad benefits to society, with support and commitment from various parties for its implementation. This study recommends several steps for the development and implementation of this model, including strengthening collaboration, program development, education enhancement, regulatory reinforcement, and monitoring and evaluation.